The structure of population life quality - Павлова Юлія Олександрівна, (Iuliia Pavlova) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to formate the conceptual life quality model that defines the basic components of human well-being. Material and Methods: theoretical analysis, scientific and methodical literaturedata generalization, sociological and statistical methods. The 300 youth respondents, 98 adults of first mature age, 290 adults of second mature age and 150 elderly people were surveyed. Results: objective and subjective component was selected in life quality; the basic components of life quality was identified. Conclusions: physical component, psychological component, social activity, material component, development and identity, environment are the basic components of quality of life